If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying x + 3x + -3y = 0 Combine like terms: x + 3x = 4x 4x + -3y = 0 Solving 4x + -3y = 0 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3y' to each side of the equation. 4x + -3y + 3y = 0 + 3y Combine like terms: -3y + 3y = 0 4x + 0 = 0 + 3y 4x = 0 + 3y Remove the zero: 4x = 3y Divide each side by '4'. x = 0.75y Simplifying x = 0.75y
| -161=-14x-9x | | X+158=180 | | 4.5-x=6 | | 2(x+3)=1-2x | | 161=14x-9x | | -3(x+5)=8+18 | | y=(2x-15)+2 | | 8y^2-18y+7=0 | | X+160=180 | | 2p-7=13+6p | | 1-7(6-5x)=4(6-x)-10X | | -5(7x+2)=-5x-40 | | -r-16r=136 | | 0.3(2h+3)=5 | | 7n^2+22n-24=0 | | 9y-2y=28 | | 10x+2=9x^2 | | n^2-6n-7=0 | | -4(m-23)=5 | | 0.8x=5.6 | | -3=10+x | | 0.6(x+1)=-8 | | 4a+-10=42 | | (5a-6)(5a-6)=0 | | 4a-10=24 | | 5w+7+3w+10=6w-9-4w+1 | | (2x-3)=3 | | -2y-10=3y+4 | | 3(x-7)=2(x+6) | | 0.6-0.1(1.41-3x)=0 | | 3(5x-2)+27=-24 | | 33+3y-4=14y-13-5y |